(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
The study investigated the leaf architecture and petiole anatomy of eight Dipterocarpus (Dipterocarpaceae) species growing in Mount Makiling Forest Reserve (MMFR) in the Philippines to delineate the species, especially during their non-flowering phase. Leaf and petiole samples from MMFR were examined following the manual on leaf architecture studies. Freehand technique was used to examine the stomata and petiole characters. A UPGMA phenogram was then generated to determine the relationships among Dipterocarpus species using 26 leaf and petiole characters. The most useful characters to delineate Dipterocarpus species are the presence of trichomes, the arrangement of vascular bundles (medullary and outer vascular bundles), areolation, fimbrial vein, and leaf size. Other characters viz., the laminar ratio, blade class, laminar shape, base shape, margin type, and intersecondary, and layers and shape of parenchyma and collenchyma cells were useful as unifying characters. Therefore, certain characters of the leaf architecture and petiole anatomy may be used as taxonomic markers to delineate and correlate the Dipterocarpus species in the Philippines particularly during the nonflowering phase of the species. However, further investigations using samples from the wild populations of the species and molecular techniques may be done to elucidate the taxonomic use of the characters presented in this study. Bangladesh J. Plant Taxon. 27(1): 1-14, 2020 (June)